let the quadratic eq ax^2 +bx + c be such that a,b,c are distinct and each of a,b,c belong to {1,2,3.....n} such that x+1 divides ax^2+ bx +c.If such quad.polynomials are < 99,then max(n)=?

a)14 b)15 c)16 d)18 e)none of these

Since, x+1 satisfies the equation ax^2+ bx+ c=0. Therefore, a(-1)^2+b(-1)+c=0. So, a - b+ c=0.

Now, a + c=b. Minimum value of b is 3. Number of quadratic equations will exceed 99 when b=12. So, the answer is none of these.

The number of non-negative integer solutions of a + b = c ---> ^{c – 1}C_{1} = c - 1. Therefore, number of solutions when c = 2, 3, 4, .., 15 = 1, 2, 3, 4, ... 14 = 105. Out of these we have to remove solutions where a and b are not distinct. it happens when c is even. The number of cases = 7. Therefore, total solutions = 105 - 7 = 98 and answer is b.

if y is an integer such that y>=4 and x=y*y -2y,then largest number that divides x*x-8x=?

If you substitute x=y^{2}-2y into x^{2}-8x you will obtain,

x^{2}-8x = (y-4)(y-2)(y)(y+2)

__If y is odd__:

then x^{2}-8x is divisible by **3**

__If y is even__:

then it has to be divisible by 2 (4!) = **48**

For the equation 4x^{2} - 2xy - 8x + y + 9 = 0, find the number of positive integral solutions.

Hi Tina,

Plese find the solution

We want to find number of positive integral solutions for (x,y) 4x^{2} - 2xy - 8x + y + 9 = 0

=>4x^{2 }- 8x + 9 = (2x - 1)y

=>y = (4x^{2} - 8x + 9)/(2x - 1) = (2x -3) + 6/(2x-1).

Only two values satisfy. **(1,5), (2,3)**

Hello Kinshuk !

a^19 + 17a - 19 = 0

a^19 = 19 -17a

similarly , b^19 = 19 - 17b ,

c^19 = 19 - 17c .....

So a^19 + b^19 + c^19 +....... = 19 - 17a + 19 - 17b + 19 - 17c +......

= 19 × 19 - 17 ( a+ b + c +....)

Sum of roots => 0

19 × 19 - 17 × 0 = 361.

Hi Gaurav ! PFA the Solution

The number of quadratic equation with leading coefficient 1 which are unchanged by squaring their roots is?

Hello Yamin ,

a and b are roots

So , a + b = a² + b²

and ab = a²b²

=> ab(ab - 1)

i) a = 0

=> b = 0 or 1

ii) b = 0

=> a = 0 or 1

iii) ab = 1

a + 1/a = a² + 1/a²

=> a⁴ - a³- a + 1 = 0

=> (a³ - 1)(a - 1) = 0

=> a = 1 or w or w²

=> b = 1 or w² or w

So, equation are x² = 0

x² - x= 0

x² - 2x + 1 = 0 and x² + x + 1 = 0

4 such equations.

If the roots of x^2 - 2ax + a^2 + a -3 are real and less than 3 then

A. a is less than two

B. a lies between 2 and 3

C. a is greater than 4

Hello Yamin,

put x = 0 in the expression x² - 2ax + a² + a - 3

it reduces to

a² + a - 3 = 0

a = -1/2 + (√13)/2 and -1/2 + √13/2

Here roots are less than 2 hence option (B) and (C) got eliminated.

Hence , Option (A ) is the correct answer .

This was very difficult question, It took an hour to solve me this question.

If eq x^3 - ax^2 + bx - a =0 has 3 real roots the what is true?

A. a=1

B. b=1

C. b not equal to 1

x³ - ax² + bx -a = 0

x² ( x - a) + b ( x-a) = 0

if , b = 1 , then the equation reduces to

x²( x - a) + (x-a) = 0

(x-a)(x² + 1) = 0

it has one real root a and two imaginary roots . hence b ≠ 1 .

Option C.

3x^2 + px + 3 has p greater tha 0. One root is square of other. Then what is the value of p?

Hello Yamin,

Sum of roots = a + a² = -p/3 ..... (1)

Product of the roots = a³ = 3/3 = 1 ... (2)

a³ -1 = 0

(a-1)( a² + a + 1 ) = 0

(a-1) = 0 or ( a² + a + 1 ) = 0

a² + a = - 1

From equation (1)

-1 = -p/3

p = 3 🙂

In what positive base b does 4×12=103 hold?

Find the condition for the equation ax^2 + bx + c = 0 for one root is n times the other

X=2+2^2/3+2^1/3, then the value of x^3-6x^2+6x?

Hello Tarishi

(x - 2) = 2⅔ + 2⅓

Cubing both sides

(x - 2)³ =( 2⅔ + 2⅓ )³

= (2⅔)³ + ( 2⅓)³ + 3•2⅔• 2⅓( 2⅔ + 2⅓ )

[( a + b)³ = a³ + b³ + 3ab ( a + b )]

6 + 3 × 2(2⅔ + 2⅓) = 6 + 6(x - 2)

x³ - 8 - 6x² + 12x = 6 + 6x - 12

x³ - 6x² + 6x = 6 - 12 + 8 = 2.

Solve the equation:x^4-2x^3+4x^2+6x-21=0 if two of its roots are equal in magnitude but opposite in sign .

If the constant term of (2x-1/x)^n is -160 ! Find n

Hello Tarishi ,

General term of (2x – 1/x)^{ n }= ^{n}C_{r} (2x)^{r} (-1/x)^{(n-r)}

^{}

=^{ n}C_{r }(2^{r}) (-1)^{(n-r)} x^{r}(1/x)^{(n-r)}

Now ,

for constant term , power of x = 0

r = n – r

n = 2r

Constant Term = ^{2r}C_{r}2^{r }(-1)^{r}= - 160

r = 3 satisfies , Hence n = 2r = 6 .